Subinhibitory concentrations of antibiotics affect cell surface properties of Streptococcus sobrinus. - Wu, Q (1995)
Several antibiotics, at subinhibitory concentrations, caused an increase in the ability of Streptococcus sobrinus to bind alpha-1,6-glucans, whereas other antibiotics decreased glucan binding. In every case, glucan binding was inversely proportional to cell surface hydrophobicity. High levels of glucan-binding activity resulted in low levels of hydrophobicity, whereas low levels of glucan binding caused high levels of cellular hydrophobicity. The results show that low concentrations of antibiotics may modulate lectin and hydrophobin adhesins in streptococci.